2018
DOI: 10.1051/0004-6361/201732354
|View full text |Cite
|
Sign up to set email alerts
|

Dust cleansing of star-forming gas

Abstract: Aims. We explore the possibility that solar chemical composition, as well as the similar composition of the rich open cluster M 67, have been affected by dust cleansing of the presolar or precluster cloud due to the radiative forces from bright early-type stars in its neighbourhood. Methods. We estimate possible cleansing effects using semi-analytical methods, which are essentially based on momentum conservation. Results. Our calculations indicate that the amounts of cleansed neutral gas are limited to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Investigating the influence of age on solar twins, Nissen (2015) found a strong correlation of α-and s-process elements abundances with stellar age, findings that were confirmed by Tucci Maia et al 2016and Spina et al (2016). According to Önehag et al (2014), if the star is formed in a dense stellar environment, the gas of the protostellar disk could have its dust cleansed before its birth by radiation of hot stars in the cluster, but recent theoretical estimates by Gustafsson (2018) have suggested that the mechanism is not significant. Gaidos (2015) associated this effect with the gas-dust segregation in the protoplanetary disk.…”
Section: Abundance Versus Condensation Temperature Trendmentioning
confidence: 89%
See 1 more Smart Citation
“…Investigating the influence of age on solar twins, Nissen (2015) found a strong correlation of α-and s-process elements abundances with stellar age, findings that were confirmed by Tucci Maia et al 2016and Spina et al (2016). According to Önehag et al (2014), if the star is formed in a dense stellar environment, the gas of the protostellar disk could have its dust cleansed before its birth by radiation of hot stars in the cluster, but recent theoretical estimates by Gustafsson (2018) have suggested that the mechanism is not significant. Gaidos (2015) associated this effect with the gas-dust segregation in the protoplanetary disk.…”
Section: Abundance Versus Condensation Temperature Trendmentioning
confidence: 89%
“…However, other hypotheses have been proposed to explain the abundance trend, such as the stellar environment in which the star was formed (Önehag et al 2014), although according to recent theoretical estimates by Gustafsson (2018) this mechanism is hardly significant; dust segregation in the protostellar disk (Gaidos 2015); the influence of the stellar age (Adibekyan et al 2014); and the planet engulfment scenario (Spina et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, grain abundance variations may be enhanced by the resonant drag instability (Squire & Hopkins 2018;Hopkins & Squire 2018a). Yet another regime of potential decoupling occurs in the neutral shell outside the H region (Gustafsson 2018), but since the drift velocity in both these cases is much less than interesting values of the stream velocity, v ∞ , neither low-Ξ regime is relevant to dust waves.…”
Section: Gas-grain Dynamics In H Regionsmentioning
confidence: 99%
“…Another possible caveat of the present model is, however, turbulence which was found by Gustafsson (2018) to be a major problem with the alternative hypothesis of massive dustcleansing by bright stars as an explanation for the Meléndez effect. The effects of turbulence on the present self-cleansing model are discussed below.…”
Section: Conclusion From the Spherically Symmetric Modelmentioning
confidence: 68%
“…This was supported by the results of Önehag et al (2011, 2014) who carried out detailed analyses of solar-twins and solar analogues in the rich, old cluster M 67, and found the cluster stars to have an abundance profile more similar to that of the Sun than most solar twins in the neighbourhood. However, Gustafsson (2018) recently found that the cleansing mechanism proposed was unlikely to be efficient enough to explain the chemical peculiarities of a relatively massive cluster like M 67. Also, the recent finding of binary stars with one component showing deviating abundances from that of the other, such as 16 Cyg (Tucci Maia et al 2014;Nissen et al 2017), XO-2N/XO-2S (Ramírez et al 2015;Biazzo et al 2015), WASP 94 A/B (Teske et al 2016a), HD 133131 A/B (Teske et al 2016b), HAT-P-4 (Saffe et al 2017) and the co-moving pair HD 240430/HD 1240429 (Oh et al 2018), and sometimes with differences correlating with the condensation temperature of the element, suggests that the phenomenon may be local.…”
Section: Introductionmentioning
confidence: 99%